Entre o “new society” e o “ xilindró”: discursos construtores de masculinidades e feminilidades na folha do norte do paraná (1965 -1973) - Silva, Gessica Aline (2018)
The present dissertation starts from questions about the limits and borders between genders, the exchanges and negotiations that involve the constitution of subjects. In this way, we analyzed the models of masculinities and femininities presented by the social column and the police column in the newspaper of the city of Maringá called Folha do Norte do Paraná between the years of 1965 and 1973. From the theoretical reference of Gender Studies, thinking about the production of masculinities and femininities, the concept of performativity of the author Judith Butler and Michel Foucault's positions on the constitution of knowledge, powers and subjects, we focused on the approach of some subjectivities that served as model and reference, being emphasized in the speeches of the press. In this context, the figures of “good men”, "ladies of society", "sluts" and "drunks" were constituted in an opposite, extreme and complete way between one and another. Through these dualities in relation to the masculine and feminine performances conveyed by the newspaper, we observed how the context of Maringá was articulated, in which the newspaper was produced, with its content and the production of meanings and subjects. When analyzing the constructions of gender present in the newspaper we noticed that these were not unanimous or corresponding directly to the region’s reality, being in fact, one of the possible readings of that time, associated and influenced by the groups involved in the production of these meanings.